2020
DOI: 10.1029/2019ms002019
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions in a Chemistry‐Climate Model: Feedbacks and Climate Response

Abstract: Understanding the past, present, and future evolution of methane remains a grand challenge. Here we have used a hierarchy of models, ranging from simple box models to a chemistry-climate model (CCM), UM-UKCA, to assess the contemporary and possible future atmospheric methane burden. We assess two emission data sets for the year 2000 deployed in UM-UKCA against key observational constraints. We explore the impact of the treatment of model boundary conditions for methane and show that, depending on other factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
5
19
0
Order By: Relevance
“…Heimann et al. (2020) previously reported a methane interhemispheric gradient of 104 ppb with a global mean methane surface mole fraction of 1590 ppb for the period 2000–2005, calculated from their BASE experiment, which is comparable to our emission‐driven simulation (cf. Heimann et al., 2020, Section 3.2).…”
Section: Model Evaluationsupporting
confidence: 88%
See 1 more Smart Citation
“…Heimann et al. (2020) previously reported a methane interhemispheric gradient of 104 ppb with a global mean methane surface mole fraction of 1590 ppb for the period 2000–2005, calculated from their BASE experiment, which is comparable to our emission‐driven simulation (cf. Heimann et al., 2020, Section 3.2).…”
Section: Model Evaluationsupporting
confidence: 88%
“…Recently, Heimann et al. (2020) showed that increased CO and methane emissions could each at least partially resolve the negative bias in carbon monoxide, but they also argue that the negative bias in CO could be due to missing higher VOC sources. However, without targeted sensitivity experiments it is difficult to conclusively attribute these biases to primary emissions of CO or to secondary in situ CO production from chemical oxidation of methane and non‐methane volatile organic compounds (NMVOC) in our model.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Natural sources include emission from agricultural lands, wetlands, marshy areas and enteric fermentation in ruminant animals. Anthropogenic sources include emission from fossil fuel extraction, landfill and various other anthropogenic activities (Janssens-Maenhout et al 2019;Heimann et al 2020). Most of the CH 4 emissions, almost to the tune of 60%, happen in the northern hemisphere, however the extended lifetime to inter-hemispheric transport lessens the north to south (N:S) latitudinal gradient of CH 4 upto 100 ppb (Heimann et al 2020).…”
Section: Ch 4 Emissions During Covid-19mentioning
confidence: 99%
“…Slower oxidation of CH 4 leads to lower δ 13 CH 4 by extending the 12 CH 4 lifetime more than that of 13 CH 4 [1][2][3][4][5][6][7]23,24 . Biogenic emissions from wetlands and permafrost 5,6,[25][26][27][28][29][30][31][32][33] and atmospheric methane lifetime 10,[20][21][22][23][34][35][36][37][38][39][40] are major methaneclimate feedbacks, while other feedback processes, such as wildfires 36,[41][42][43][44] and natural thermogenic emissions 45 , are considered secondary 6,7 . The methane-lifetime feedback contributes the highest uncertainty in estimates of feedback strength 7,40 .…”
mentioning
confidence: 99%
“…Nevertheless, exceptions apply. For example, with respect to LSAT, the atmospheric sink provides secondary positive feedback: higher CH 4 emissions, with positive feedback via biomass burning 41,42,44 , result in increased atmospheric carbon monoxide (CO), reacting with atmospheric • OH to decrease its concentration, hence extending the CH 4 lifetime 22,36,37 . Similarly, increased emissions of biogenic volatile organic compounds (BVOCs) result in positive feedback by limiting • OH 40 .…”
mentioning
confidence: 99%